Reactive Power Compansation By PWM-Statcom - Coteli, Resul; Aydogmus, Zafer (Gazi Univ, 2007)
In recent years, FACTS (Flexible Alternating Current Transmission Systems) devices are used for reactive power compensation in power systems, transmission and distribution systems, since their response is faster than that of the conventional compensators. One of the most widely used FACTS device is STATCOM. In this study, simulation of the STATCOM (Static Synchronous Compensator) has been realized by using Pulse Width Modulation (PWM). Matlab-Simulink software is used for simulation. In the simulation, dynamic response of PWM-STATCOM has been observed for various bus voltages. From the results of the simulation, it has been observed that response of the PWM-STATCOM to instant variations is very fast and reactive power for power system is provided in short time.
Keywords: Compensation; PWM-STATCOM